2009
DOI: 10.1111/j.1532-950x.2009.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Inhibitory Concentration and Postantibiotic Effect of Amikacin for Equine Isolates of Methicillin‐Resistant Staphylococcus aureus In Vitro

Abstract: Clinical isolates of MRSA are susceptible to amikacin at concentrations achieved by regional perfusion: however, the modest duration of PAE observed suggest that further laboratory and in vivo evaluation be conducted before recommending the technique for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…A PAE of aminoglycosides lasting up to 8 h has been reported (Begg and Barclay 1995;Lacy et al 1998;Fisman and Kaye 2000). Caron et al (2009), however, reported in an in vitro study that 6 strains of methicillin-resistant Staphylococcus aureus had a much shorter PAE (mean PAE 3.4 h). Renneberg and Walder (1989) reported the PAE for a single strain of Staphylococcus aureus treated with 10 mg/kg bwt amikacin in an in vivo mouse model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A PAE of aminoglycosides lasting up to 8 h has been reported (Begg and Barclay 1995;Lacy et al 1998;Fisman and Kaye 2000). Caron et al (2009), however, reported in an in vitro study that 6 strains of methicillin-resistant Staphylococcus aureus had a much shorter PAE (mean PAE 3.4 h). Renneberg and Walder (1989) reported the PAE for a single strain of Staphylococcus aureus treated with 10 mg/kg bwt amikacin in an in vivo mouse model.…”
Section: Discussionmentioning
confidence: 94%
“…1998; Fisman and Kaye 2000). Caron et al . (2009), however, reported in an in vitro study that 6 strains of methicillin‐resistant Staphylococcus aureus had a much shorter PAE (mean PAE 3.4 h).…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by the few studies in the literature with MIC data. Caron et al published on the MIC of methicillin resistant S. aureus isolates from horses where the MIC varied from 2 to 32 μg/mL. Another study reported that all Gram‐negative bacterial isolates from equine neonates had an MIC 90 of 4 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoglycosides are known to exert a postantibiotic effect (PAE), defined as the continued suppression of bacterial growth after limited exposure of the organism to an antibiotic . A range of PAE durations for amikacin have been reported in the literature . Isaksson et al reported mean PAE against staphylococci of 5–10 hours for clinically achievable aminoglycoside concentrations, and the duration of the PAE increased with increasing aminoglycoside concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation